2009
DOI: 10.1111/j.1365-2699.2008.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the brown hare (Lepus europaeus) in Europe: a legacy of south‐eastern Mediterranean refugia?

Abstract: Aim We analysed the population genetics of the brown hare (Lepus europaeus) in order to test the hypothesis that this species migrated into central Europe from a number of late glacial refugia, including some in Asia Minor.Location Thirty-three localities in Greece,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
91
1
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 41 publications
14
91
1
15
Order By: Relevance
“…Given that hybridization between Lepus species in Europe is a common phenomenon (Alves et al 2003Melo-Ferreira et al 2005Zachos et al 2010) we tried to verify whether hybrids occurred between and among the two Lepus species from Switzerland, searching for mtDNA introgression. Using methods of mtDNA analysis previously described (Stamatis et al, 2007(Stamatis et al, , 2009, we detected seven out of 133 (5.263%) L. europaeus individuals with the most common L. timidus mtDNA haplotype and five out of 92 (5.434%) L. timidus individuals with the most common L. europaeus mtDNA haplotype. Further comparative analysis of MC1R and mtDNA data revealed that the two L. timidus individuals with the L. europaeus MC1R sequence bore also a L. europaeus mtDNA haplotype and the same was true for one of the two heterozygous (L. europaeus/L.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Given that hybridization between Lepus species in Europe is a common phenomenon (Alves et al 2003Melo-Ferreira et al 2005Zachos et al 2010) we tried to verify whether hybrids occurred between and among the two Lepus species from Switzerland, searching for mtDNA introgression. Using methods of mtDNA analysis previously described (Stamatis et al, 2007(Stamatis et al, , 2009, we detected seven out of 133 (5.263%) L. europaeus individuals with the most common L. timidus mtDNA haplotype and five out of 92 (5.434%) L. timidus individuals with the most common L. europaeus mtDNA haplotype. Further comparative analysis of MC1R and mtDNA data revealed that the two L. timidus individuals with the L. europaeus MC1R sequence bore also a L. europaeus mtDNA haplotype and the same was true for one of the two heterozygous (L. europaeus/L.…”
Section: Resultsmentioning
confidence: 96%
“…Previous wide-ranged phylogenetic studies using the same set of L. europaeus samples as in the present study and based on both maternally (mtDNA) and/or paternally (SRY) transmitted molecular markers, have shown a deep phylogeographic separation, at least, between Europe and Anatolia (Mamuris et al 2010;Stamatis et al 2008Stamatis et al , 2009. Although several hares from Turkey and especially from the Ş anlıurfa region reported to have a generally yellowish fur, very similar to hares from the semiarid Be'er Sheva region in south-central Israel, north of the Negev desert (Suchentrunk et al 2000;Yom-Tov 1967), MC1R analysis failed to reveal any difference; all Turkish L. europaeus populations surveyed, regardless of their origin, bore the same MC1R allele as the European ones.…”
Section: Discussionmentioning
confidence: 95%
“…Starting with Thulin et al[7], several molecular studies have identified patterns of reticulate evolution and paraphyly in a number of Lepus species, both on the intraspecific (e.g., Kasapidis et al[14]; Stamatis et al[15]) and interspecific levels (e.g., Alves et al[8,16], Thulin et al[17], Melo-Ferreira et al[18], Wu et al[19], Fredsted et al[20], Ben Slimen et al[21]; Melo-Ferreira et al[22], Alves et al[23,24], Pietri et al[25], Zachos et al[26], Liu et al[9], Wu et al[27], Melo-Ferreira et al[28], Melo-Ferreira et al[10,11], Mengoni et al[29]). This may add to systematic ambiguity or confusion, particularly if phylogenetic conclusions are based solely on mtDNA data (e.g., Waltari and Cook[30]; Wu et al[19], Ben Slimen et al[31]) or geographically limited sample sizes, or when molecular samples are analyzed without concomitant phenotypic examination.…”
Section: Introductionmentioning
confidence: 99%
“…In the Iberian Peninsula, this species is restricted to the Pyrenean foothills, but has a broad distribution north of the Pyrenees. This species likely invaded Iberia only when it colonised Western Europe (Stamatis et al, 2009) after the last glacial maximum, a period characterised by major range changes of numerous European taxa promoted by deglaciation (Hewitt, 2000). Iberian populations of this species harbour very high frequencies of mtDNA of L. timidus origin, which appears almost fixed (Melo-Ferreira et al, 2005;Alves et al, 2008).…”
Section: Introductionmentioning
confidence: 99%